Investigating Teacher’s Perceptions of Reflective Peer Observation to Promote Professional Development - Cholifah, Anjar Nur; Asib, Abdul; Suparno, Suparno (JEES (Journal of English Educators Society), 2020)
Peer observation as one of the reflection tools is viewed as an effective strategy to develop teacher’s professionalism. Furthermore, peer observation in reflective practice refers to the teacher’s act which collaborates with other teachers to identify the strength and the weakness of their teaching. By doing so, it is expected there will be innovation and improvement for better teaching activity after doing an evaluation together. This study aimed at investigating the teacher’s perceptions of peer observation as one of the reflection tools to promote professional development. The participant of this study was an In-service teacher in one of Senior High Schools in Surakarta who teaches English with 10 years of teaching experience. The data were gained through an in-depth interview followed by interactive model data analysis for qualitative study in analyzing the data. The results indicated that the teacher has positive perceptions of peer observation as a professional development tool. It brought some advantages for the teacher. Peer observation also helped the teacher to solve the problems she encountered in her teaching and could be used as a learning opportunity by observing new teaching techniques/methods/strategies from other teachers. HIGHLIGHTS: Teacher has positive perceptions in implementing peer observation to promote professional development There are limited studies regarding the use of peer observation especially for in-service teacher Peer observation brings some benefits for the teacher to improve her teaching practice